N or M? - Christie, Agatha (London Fontana/Collins, 1990)
Tommy & Tuppence are hired to track down wartime spies at a seaside resort...
Keywords: Beresford, Tommy (Fictitious character) -- Beresford, Tuppence (Fictitious character) -- Private investigators